Selective Enforcement in the Criminal Justice System: Between Discretion and Abuse of Authority - Thahir, Thahir; Sucipto, Muh. Adi; Riyanto, Ontran Sumantri (Jurnal Hukum dan Keadilan, 2025)
Selective enforcement has become an increasingly prominent phenomenon in the practice of criminal justice systems, particularly alongside the expansion of discretionary powers held by law enforcement authorities. While discretion is fundamentally necessary to ensure flexibility and substantive justice, in practice it often evolves into selective application of the law toward normatively similar criminal acts. This study aims to analyze the position of selective enforcement within the frameworks of criminal law and administrative law and to determine the normative boundary between lawful discretion and abuse of authority. This research employs a normative juridical method using statutory, conceptual, and case approaches. The findings reveal a significant ambiguity of norms governing law enforcement discretion under the Criminal Procedure Code, Law Number 11 of 2021 on the Prosecutor’s Office, and Law Number 1 of 2023 on the National Criminal Code. Such normative ambiguity creates opportunities for abuse of authority as prohibited under Law Number 30 of 2014 on Government Administration. Selective enforcement has been shown to undermine the principles of equality before the law, legal certainty, and the legitimacy of the rule of law. This study concludes that selective enforcement constitutes a serious normative problem that requires clear regulatory limits on discretion and the strengthening of accountability mechanisms within the criminal justice system.